REPRESENTAÇÕES SOCIAIS DE PROFESSORES DE DIREITO SOBRE O EXERCÍCIO DA DOCÊNCIA - Moraes, Patrícia Regina de (2012)
The objective of this study is to investigate the social representations of law professors about the teaching profession. We tried to understand what the teacher knowledge that the law professor deems necessary for its operation, since the legislation does not require the operator of the common law a specific course to enable him to teach in higher education. For this reason, generally, the law professor is faced with numerous difficulties in the early stage and notes that, in practice, be a good professional law is not enough to teach, because it requires a didactic and pedagogical method by which students understand it. The research had as subjects of law professors who are teaching in at least two years ago in São Paulo and the Greater ABC. The authors who made possible the theoretical framework were: Serge Moscovici (1978), Denise Jodelet (2005), questions were presented, three open and closed twelve. From the descriptions of the responses given by subjects in the questionnaire, it was possible to analyze the data collected through the content analysis (Laurence Bardin, 1977). The survey allowed the analysis of perception and conception of the subjects Marilia Claret Geraes Duran (2006), among other significant studies. The study was conducted using qualitative and quantitative research data. For data collection, a questionnaire was used in its initial part, had three words inducing. Then, fifteen regarding the legal education and their own training. Demonstrated further that the law professor needs to take ownership of specific knowledge teachers to teach, beyond the idea that you just technical knowledge, since that teaching, like other professions, has important peculiarities.